Palm oil based nanofluids for enhancing heat transfer and rheological properties - Hussein, Adnan M.; Lingenthiran, Samylingam; K., Kadirgama; M. M., Noor; Aik, L. K. (Springer-Verlag, 2018)
Colloidal suspensions of nanomaterials size not more than 100 nm in basefluid are defined as nanofluids. The thermal and rheological properties study of oil based nanofluid is conducted to develop stable transformers palm oil based nanofluid. This paper describes the analysis techniques to determine the enhancement of thermal properties of nanofluids. Titanium dioxide (TiO2) has dispersed in the palm oil to prepare nanofluids with volume concentration (0.01–0.09) percentage. Both thermal conductivity and viscosity of nanofluid have measured by using the hot wire method and viscometer equipment respectively. Results indicate that the stable nanofluids improve the thermal properties as compared to palm oil. Results showed that the friction factor decreases as the Reynolds number increases and increases as the volume concentration increases. Additionally, the Nusselt number increases as the Reynolds number and volume concentration of the nanofluid increases.